2012
DOI: 10.1111/j.1399-3038.2012.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Few associations between high‐sensitivity C‐reactive protein and environmental factors in 4.5‐year‐old children

Abstract: We found few associations between early environmental farming factors and hsCRP levels, and between hsCRP levels and atopic sensitization in 4.5-year-old children. However, our results suggest that the role played by the environmental factors in low-grade inflammation may differ between sensitized and non-sensitized children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The six food allergens were hen's egg, cow's milk, peanut, hazelnut, carrot, and wheat. Any allergic sensitization was defined as a positive result [sIgE concentration of 0.35 kU/l or greater at the age of 1 yr and 0.70 kU/l or greater at the age of 4.5 yr ] to any of the tested allergens. Inhalation or food atopy was defined as a positive result to any of the 13 inhalation or six food allergens tested, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The six food allergens were hen's egg, cow's milk, peanut, hazelnut, carrot, and wheat. Any allergic sensitization was defined as a positive result [sIgE concentration of 0.35 kU/l or greater at the age of 1 yr and 0.70 kU/l or greater at the age of 4.5 yr ] to any of the tested allergens. Inhalation or food atopy was defined as a positive result to any of the 13 inhalation or six food allergens tested, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of 277 Danish children, higher hs-CRP levels at 7 years was associated with an elevated risk of concurrent allergic rhinitis, asthma, and sensitization to aeroallergens, food allergens, or any allergen; yet, no associations were observed between CRP levels at 6 months with later development of allergic outcomes until 7 years [6]. However, in 2 analyses by Mustonen et al [4, 5], children with elevated hs-CRP levels were at a decreased risk of allergic sensitization, though not with atopic dermatitis and asthma. In addition, a study of 4,111 US children and adolescents (2–19 years) reported that increased hs-CRP levels were significantly associated with an elevated risk of atopy and food allergy [7].…”
Section: Discussionmentioning
confidence: 99%
“…material, see www.karger.com/doi/10.1159/000497320) [3-7]. Most of these studies adopted a cross-sectional design [3, 4, 7] and had a small sample size [3-6]. Therefore, we sought to re-examine the interrelation between hs-CRP levels and allergic outcomes using a larger population size and a longitudinal study design.…”
Section: Introductionmentioning
confidence: 99%
“…The food allergens were cow's milk, hen's egg, hazelnut, peanut, wheat, and carrot. Any allergic sensitization was defined as a positive result, i.e., sIgE concentration of 0.35 kU/l or greater at the age of 1 yr and 0.70 kU/l or greater at the age of 6 yr , to any of the tested allergens. Inhalation or food atopy was defined as a positive result to any of the inhalation or food allergens, respectively.…”
Section: Methodsmentioning
confidence: 99%